2014
DOI: 10.1080/13603116.2013.879216
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' attitudes to signing for children with severe learning disabilities in Indonesia

Abstract: Abstract.The Indonesian education system is striving for an inclusive approach and techniques are needed which can support children with severe learning disabilities and their peers in this context. Manually signed language has proved useful both in supporting the development and empowerment of children with severe learning disabilities and supporting inclusive educational practices. The development of an Indonesian signed language approach for this purpose is therefore argued to be an appropriate goal.There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 19 publications
2
41
2
4
Order By: Relevance
“…This finding is marginally different from studies conducted with teachers and classroom assistants which revealed considerable individual variation in the attitudes of school staff towards KWS (Sheehy & Budiyanto, ; Sheehy & Duffy, ). Although most participants in previous studies expressed an understanding of the value of KWS, some did not understand its true value, believing instead that KWS was detrimental to speech and of limited use in the wider environment (Sheehy & Budiyanto, ; Sheehy & Duffy, ).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is marginally different from studies conducted with teachers and classroom assistants which revealed considerable individual variation in the attitudes of school staff towards KWS (Sheehy & Budiyanto, ; Sheehy & Duffy, ). Although most participants in previous studies expressed an understanding of the value of KWS, some did not understand its true value, believing instead that KWS was detrimental to speech and of limited use in the wider environment (Sheehy & Budiyanto, ; Sheehy & Duffy, ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Communication partners who are not fully convinced of the potential value of manual signing are unlikely to encourage a child to use this approach. To date, two studies have addressed these attitudes, by researching the perspectives of teachers and classroom assistants (Sheehy & Budiyanto, 2014;Sheehy & Duffy, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapter 5 of the thesis includes the published manuscript for the study '"I've had a love-hate, I mean mostly hate relationship with these PODD books": Parent perceptions of (Raghavendra, Virgo, Olsson, Connell, & Lane, 2011;Sheehy & Budiyanto, 2014). This disability may be due to physical, psychological, and/or cognitive impairments (Thirumanickam, Raghavendra, & Olsson, 2011).…”
Section: Thesis Overviewmentioning
confidence: 99%
“…Screening agreement between the three authors was 87.18%, and consensus for all articles was reached following group discussion. One additional article (Balandin et al, 2001) was identified for inclusion upon reviewing the reference lists of the included articles, and two articles were added from the researcher's personal library (San & Abdullah, 2013;Sheehy & Budiyanto, 2014). This totalled 43 articles for inclusion in the review.…”
Section: Identification and Classification Of Relevant Studiesmentioning
confidence: 99%